Zastosowanie modelu MESS w przestrzenno-czasowej analizie stopy bezrobocia w Polsce; Application of the MESS model in space-time analysis of the unemployment rate in Poland - Iwona Muller-Fraczek; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2013)
– The purpose of the article was a space-time analysis of the unemployment rate in polish poviats. In the research we use a model in which spatial dependence is represented in the exponential form, based on the neighborhood matrix. This model, called the Matrix Exponential model, was proposed by J.P. LeSage and R.K. Pace in 2007. It is characterized by simplicity of estimation, which can compete with other known approaches. The presented analysis was a continuation of previous purely spatial studies (Müller-Fraczek, Pietrzak 2011b). This article consists of three parts. Each of them provides an analysis of the unemployment rate registered in Poland at the end of the years 2004-2009. In the first part the unemployment rate was analyzed for each year separately. Almost linear changes of parameters of the space models, allowed us to build a space-time matrix exponential model MESS. It was described in the second part of the article. In the last part the results, obtained using the MESS model, were confronted with an approach based on space-time autoregressive model.
Keywords: C21; R11; R23; J64; 330; spatial econometrics; spatial autocorrelation; spatial model MESS; space-time analysis of the unemployment rate; spatial dependence